2005
DOI: 10.1038/sj.ejcn.1602109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-carnitine on plasma glycemic and lipidemic profile in patients with type II diabetes mellitus

Abstract: Objective: We designed this study to investigate the effects of oral L-carnitine administration on fasting plasma glucose (FPG), glycosylated hemoglobin (HbA1c) and lipid parameters in patients with diabetes mellitus type II. Patients and methods: The effect of L-carnitine on FPG and lipid parameters was investigated in 22 male and 13 female type II diabetic patients; the mean age7s.d. was 51.373.7 y. The patients were randomly allocated to two groups (L-carnitine and placebo group) and 1 g of L-carnitine or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 24 publications
3
45
2
3
Order By: Relevance
“…Taken together, the two investigations provide compelling evidence that oral carnitine supplements administered to obese rodents not only restores tissue carnitine content, but also enhances glucose disposal and mitochondrial performance. A limited number of small scale clinical studies have likewise reported positive outcomes of L-carnitine therapy in humans (43)(44)(45). In these studies, acute carnitine infusion during a hyperinsulinemic-euglycemic clamp was found to increase glucose disposal and whole body carbohydrate oxidation in insulin-resistant subjects (43,44).…”
Section: Discussionmentioning
confidence: 85%
“…Taken together, the two investigations provide compelling evidence that oral carnitine supplements administered to obese rodents not only restores tissue carnitine content, but also enhances glucose disposal and mitochondrial performance. A limited number of small scale clinical studies have likewise reported positive outcomes of L-carnitine therapy in humans (43)(44)(45). In these studies, acute carnitine infusion during a hyperinsulinemic-euglycemic clamp was found to increase glucose disposal and whole body carbohydrate oxidation in insulin-resistant subjects (43,44).…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, a study from China [11] and another from Italy [12] found that carnitine lowered circulating lipids but did not improve fasting glucose levels. A recent study conducted in Iran [13] reported that dietary carnitine lowered fasting glucose levels, but increased triacylglycerol levels.…”
Section: Introductionmentioning
confidence: 99%
“…Препарат не купировал и не провоцировал нарушения ритма сердца и проводимости. Его вве-дение хорошо переносилось больными, включая пациентов с сахарным диабетом, что соответству-ет литературным данным [17]. Не случайно лево-карнитин с успехом используют также при ожи-рении и в спортивной медицине.…”
Section: характеристика пациентов по группам исследованияunclassified